The Influence of Location and Marketing Strategy on Purchase Decisions - Lokot Muda Harahap; Khafi Puddin (LPPM STIE EKA PRASETYA, 2022)
This study aims to determine the effect of Location and Marketing Strategies on Purchasing Decisions on Pizza Boy Adam Malik Medan. The population in this study are all consumers who have made purchases at Pizza Boy Adam Malik Medan in 2019. Using the Slovin formula with an error rate of 10%, a total sample of 99 respondents was obtained. The results of the research analysis showed that Location and Marketing Strategies partially and simultaneously have a positive and significant effect on Purchasing Decisions at Pizza Boy Adam Malik Medan. The results of this study are supported by the value of R square (R2) which means that the Location and Marketing Strategy has an effect on the Purchasing Decision at Pizza Boy Adam Malik Medan. While the remaining is effected by other factors originating from outside this research model such as taste quality, service quality, price discounts, advertising, product variations, pricing, consumer behavior, consumer perceptions and product trust.